Asymptotic behavior of the best approximations for the functions in $L_p$ - Pichugov, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The asymptotic behavior of the ratio $E_n (f)_p/ω(f, α/ n)_p$ is studied for individual periodic functions $f \in L_p$.